From students to leaders: evaluating the impact on academic performance, satisfaction and student empowerment of a pilot PAL programme among first year students and second year leaders - Stacey Scriver (Association for Learning Development in Higher Education (ALDinHE), 2015)
This paper evaluates the pilot year of the CÃâ°IM PAL initiative at the National University of Ireland Galway through analysis of examination results, student surveys and the reflections of two students who participated as first year students in the pilot year and subsequently as student leaders in year two. The paper considers the impact of attendance at sessions on academic performance, student satisfaction with the programme, and evaluates the extent to which the initiative has assisted students to become more empowered learners as expressed through the development of self-directed learning, growth in educational self-efficacy, and confidence in navigating the learning environment. Recommendations are also made for developing the CÃâ°IM initiative, which may be relevant to other PAL programmes and for determining the direction of future research.